S100A8/A9 in Myocardial Infarction: A Promising Biomarker and Therapeutic Target - Cai, ZhuLan; Xie, Qingwen; Hu, Tongtong; Yao, Qi; Zhao, Jinhua; Wu, Qingqing; Tang, Qizhu (Frontiers in Cell and Developmental Biology, 2020)
Myocardial infarction (MI), the main cause of cardiovascular-related deaths worldwide, has long been a hot topic because of its threat to public health. S100A8/A9 has recently attracted an increasing amount of interest as a crucial alarmin that regulates the pathogenesis of cardiovascular disease after its release from myeloid cells. However, the role of S100A8/A9 in the etiology of MI is not well understood. Here, we elaborate on the critical roles and potential mechanisms of S100A8/A9 driving the pathogenesis of MI. Firstly, cellular source of S100A8/A9 in infarcted heart is discussed. Then we highlight the effect of S100A8/A9 heterodimer in the early inflammatory period and the late reparative period of MI as well as myocardial ischaemia/reperfusion injury. Moreover, the predictive value of S100A8/A9 for the risk of recurrence of cardiovascular events is elucidated. Therefore, this review focuses on the molecular mechanisms of S100A8/A9 in MI pathogenesis to provide a promising biomarker and therapeutic target for MI.